The Display Of Museum Sandi Yogyakarta - Akeyla, Bertha Arista; Dartanto, A. Sudjud; Kirana, Dian Ajeng (TUMATA: Journal of Cultural and Arts Management, 2024)
Museum Sandi is a special government museum managed by the Badan Siber dan Sandi Negara (BSSN), which was inaugurated in 2014. The museum has eight types of collections which are divided into nine exhibition rooms. Each room has a theme based on the collection it is arranged in. The aim of this research is to find out related matters in the display system at the Museum Sandi. The research method used is a qualitative research method with a theoretical approach to museum exhibition layout. Data was collected using direct observation methods, semi-structured interviews, and literature studies. The results of the research reveal that matters related to museum exhibition layout include supporting elements and aspects which are arranged in the form of: space, floor-space design and visitor circulation, exhibition text and labeling, work material and storyline, lighting, as well as facilities and supporting visual elements. Based on the research results, it can be concluded that the Museum Sandi's display system uses the rules for using cultural heritage buildings. This consideration of building intervention and space adaptation is applied to present the collection.